The Role of Gunawan Setiawan's Batik Industry in the Education Process and Maintaining Batik Cultural Symbols in the Community - Renzi Noviana; Omy Marissa Verdiani; Mohamad Rizki Azhar; Yosafat Hermawan Trinugraha; Bagas Narendra Parahita (Gondang: Jurnal Seni dan Budaya, 2024)
Batik is one of the handicrafts that has high artistic value which has been passed down from generation to generation by the ancestors of the Indonesian nation since the Majapahit Kingdom and continues to be preserved today. However, we have discovered the reality that currently there are still many people who do not fully understand the meaning or philosophy behind batik motifs. Through this, it is necessary to have an educational process for the community, one of which can be carried out by the batik industry. The purpose of this study is to provide an overview regarding how the educational process carried out by Kampung Batik Kauman, especially Batik Gunawan Setiawan, is to provide a comprehensive understanding of batik to the public. This research was conducted in Surakarta, namely in Kauman Batik Village, precisely in Gunawan Setiawan Batik. The research method used is a qualitative research method with a case study approach. The results showed that there were several educational processes carried out by Batik Gunawan Setiawan, such as creating a batik gallery, conducting batik exhibitions and holding batik training. Furthermore, the process of batik education in the community is analyzed using Structural-Functional Theory - Radcliffe Brown as a countermeasure to tensions. As he stated that culture is not to satisfy individuals but to fulfill the social structure of society and emerge to overcome tensions such as theft of cultural identity due to the lack of public concern regarding local culture.